Clinical outcomes of cryptozoospermic patients undergoing surgical sperm retrieval - Kaiyal, Raneen Sawaid; Cannarella, Rossella; Kuroda, Shinnosuke; Parekh, Neel V.; Vij, Sarah C.; Lundy, Scott D. (Frontiers in Urology, 2023)
INTRODUCTION AND OBJECTIVE: Cryptozoospermia is defined by the World Health Organization (WHO) as the presence of isolated sperm cells in the ejaculate only identified after an extended microscopic search or after being pelleted. Although the amount of spermatozoa is usually sufficient for intracytoplasmic sperm injection (ICSI), ICSI fails due to poor sperm quality in some cases. Contention remains regarding whether testicular sperm offers any advantage in this unique situation. At our tertiary referral center, we will offer patients a surgical sperm retrieval via conventional or microdissection testicular sperm extraction (microTESE) for men with cryptozoospermia and failed ICSI or where ejaculated specimens are immotile or insufficient for ICSI. In this study, we sought to describe our experience and evaluate the predictors of success in cryptozoospermic patients who had microTESE at our center. METHODS: We retrospectively reviewed our electronic medical records for all patients with cryptozoospermia who underwent microTESE between 2007- 2021 for failed ICSI with ejaculated sperm or sperm quality deemed to be of insufficient quality for ICSI (e.g., nonmotile sperm). We evaluated demographics, preoperative lab results, pathology results, sperm retrieval rate (SRR) and ICSI outcomes. RESULTS: 28 cryptozoospermic patients were identified. These patients underwent 37 unique microTESE. 22 of these men had failed previous ICSI treatment with ejaculated sperm, while the other six patients had ejaculated sperm with non-suitable quality for ICSI. None had genetic abnormalities. Successful retrieval of motile sperm suitable for ICSI was achieved in 30 micro TESE procedures (SRR: 81.0%) .14 out of 28 patients (50%) who underwent embryo transfer had positive pregnancy results, and 12/28 patients (42.8%) had a successful live birth. The most common pathological pattern was hypospermatogenesis, found in 65.3% (17/26). Fibrosis pathology was significantly higher in the negative pregnancy group. There were no postoperative complications noted. CONCLUSIONS: The use of testicular sperm in cryptozoospermic men with failed prior ICSI using ejaculated sperm has a high rate of pregnancy and live birth. While still controversial, our results suggest that a surgical sperm retrieval is a viable option for these men with minimal risk of complications.